JENIS-JENIS KALIGRAFI PADA DINDING-DINDING MASJID - Ruwiyah Zamzam; As Sauti Wahid (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is an art in writing that produces beautiful writings. Calligraphy is nothing new especially in Islam. Calligraphy in Islam is used to write verses of the Quran in Arabic. In Arabic, calligraphy is known as Khat. Calligraphy consists of eight types, namely Tsulus, Naskhi, Farisi (Ta'liq), Diwani, Diwani Jali, Riq'ah, Ijazah, and Kufi. The purpose of this study was to find out which type of khat is used on the walls of mosques as decoration. This research uses the Library Research method or literature study. The data obtained is then analyzed by descriptive analysis. Of the eight types of khat, there are two types that are often used as mosque wall decorations, namely Naskhi and Kufi styles. The use of these two types of khat is due to their beautiful and simple shapes compared to other types of khat. Often used as mosque wall decorations, namely Naskhi and Kufi styles. The use of these two types of khat is due to their beautiful and simple shapes compared to other types of khat.often used as mosque wall decorations, namely Naskhi and Kufi styles. The use of these two types of khat is due to their beautiful and simple shapes compared to other types of khat.